2020
DOI: 10.1177/0196859920977113
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Surveillance Failures of Wearable Communication

Abstract: By discursively analyzing blogs and popular press articles written by people who discontinued using Fitbit, this article reveals the incongruities between the tracking of our bodily information, the communication of that bodily information via wearables, and the promises of changing of users’ attitudes and behaviors with how wearables are actually used in practice. The discourses of discontinuance in this analysis also reveal how former Fitbit engenders feelings of disconnection and may affect users in detrime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The need to consider potentially negative outcomes from social comparison however are important. Social comparison can have negative effects on body image and mental health (Scheid and Lupien, 2021;Zimbars, 2021;Russell et al, 2023). While research generally views the desire to engage in more exercise as a good thing, Russell et al (2023) note that social comparison may encourage exercise to the detriment of individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to consider potentially negative outcomes from social comparison however are important. Social comparison can have negative effects on body image and mental health (Scheid and Lupien, 2021;Zimbars, 2021;Russell et al, 2023). While research generally views the desire to engage in more exercise as a good thing, Russell et al (2023) note that social comparison may encourage exercise to the detriment of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Li et al (2019) found that when users compared themselves to someone outperforming them, it could lead to frustration and decrease use. Further, past work has identified concerns related to WHT use in terms of mental health and body image (Scheid and Lupien, 2021;Zimbars, 2021). While Russell et al (2023) did find that participants who used the running app Strava considered social comparison as a motivator to use the app more, participants also expressed concern about the negative impacts from comparison, including greater feelings of anxiety and sadness.…”
Section: Social Comparisonmentioning
confidence: 99%
“…Wearable activity trackers prompted users to engage in social competition, but this caused a reduction of self-efficacy in users who performed poorly in the competition (Rieder et al 2021). Fitbit users reported that focusing on goals, especially unmet goals, made them experience a sense of disconnection from their body's internal signals and their real personal objectives (Zimdars 2021).…”
Section: Negative Health-related Outcomesmentioning
confidence: 99%
“…The COVID-19 pandemic's emphasis on mobile media such as community contact tracing apps positioned wearable technologies as means of assessing individuals’ health and tracking locations (de Souza e Silva & Xiong-Gum, 2023; Gilmore, 2021). Wearables have also been studied in research on location tracking (Beattie & Cassidy, 2021; Gilmore, 2020) as well as surveillance (Zimdars, 2021).…”
Section: Deathlogging and Dataficationmentioning
confidence: 99%